Identification of pests in the olive culture using remote perception with an air vehicle not tripulated in the valley La Yarada Los Palos - Gallardo Torres, Joe Edmundo (2019)
This pest identification project using remote sensing with an unmanned aerial vehicle will show the scope that can be achieved in the field of agriculture and that are being used. The project has as its first stage the custom conditioning of the unmanned aerial vehicle composed of a flight structure and a camera system which will allow us to acquire data, in this case aerial images. Once the air vehicle is conditioned, the flight plans for the acquisition of images are established. This stage is delimited by the olive cultivation area that we want to evaluate. Once the conditioning has been completed and after executing the flight plans, the images are processed under two algorithm models, the results of which will eventually be interpreted in search of the identification of pests in the cultivation of the olive tree.